Analysis Of The Influence Of Discipline, Culture, And Job Satisfaction On Employee Performance At The Airport Implementation Unit For Pioneer Air Transport Services In The Sorong Raya Region, Southwest Papua - Kokali, Johni; Ismail, Tubagus; Geraldina, Ira (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
This research relates to employee performance which is an important element in achieving organizational goals. This research aims to analyze the influence of discipline, culture and job satisfaction on employee performance at the Pioneer Air Transport Service Airport Organizing Unit Office for the Greater Sorong Region. This research is descriptive quantitative research. The sample used in this research was 38 people. Sample selection used the saturated sampling method. The data analysis method uses Partial Least Square (PLS). The research results show that discipline, culture and job satisfaction have a significant effect on employee performance. Discipline, culture and job satisfaction, while the results of the analysis show that simultaneously work discipline, work culture and job satisfaction have a significant effect on employee performance. It is hoped that the results of this research can be used as input and consideration for leadership in making decisions to improve and improve employee performance at the Pioneer Air Transport Services Airport Organizing Unit Office for the Greater Sorong Region - Southwest Papua Province.